Ethambutol-induced optic neuropathy - Kyncl, Martin; Fus, Martin; Lestak, Jan (Biomedical papers, 2023)
Purpose. A case report of a 40-year-old patient with tuberculosis treated with ethambutol is described. Within six months of starting treatment, there was a painless sudden decline in visual function. Despite the known complications of ethambutol treatment, it was discontinued after another three months.Methods. In the case report, we highlight the damage to the dominantly peripheral visual pathways. Using electrophysiological examinations, we showed a significant alteration in the optic nerves. Optical Coherence Tomography (OCT) showed progressive loss of vessel density and nerve fibre layer of retinal ganglion cells. Perimetric examination showed both a central decrease in sensitivity and mainly scotomas in the temporal parts of the visual fields. Although there was improvement in visual fields over time, OCT findings indicated progression of ethambutol-induced optic neuropathy (EON). Magnetic Resonance Imaging confirmed the alteration in the peripheral part of the visual pathway (intraorbital, intracranial parts of optic nerves, chiasma, and optic tracts).Conclusion. Even though EON is not an unknown complication, new cases still occur and, unfortunately, with an irreversible course. Therefore, it is important to draw attention constantly to this complication and to consider it not only in ophthalmologists' surgeries.
Keywords: ethambutol; optic neuropathy; vessel density; magnetic resonance imaging